Does supplemental feeding affect the viability of translocated populations? The example of the hihi - Chauvenet, A; Ewen, J; Armstrong, D; Coulson, T; Blackburn, T; Adams, L; Walker, L; Pettorelli, N (2012)
Translocations are commonly used conservation actions that aim at establishing new, self-sustaining populations of threatened species. However, many translocated populations are not self-sustaining but managed through supplemental feeding from the onset. Often, the decision to start managing is ad hoc, but managers will eventually have to make decisions for the future, for example, stop intervening, continue as it is or change the quantity of food provided. Such a decision requires managers to quantify the importance of supplemental feeding in determining the performance and population dynamics of translocated populations, information that is rarely available in the published literature. Using the hihi as a case study, we examined the importance of supplemental feeding for the viability of a translocated population in New Zealand. We found that supplemental feeding positively affected the survival and abundance of translocated adult hihi but also found evidence of negative density dependence on recruitment. We present two stochastic population models that project the hihi population under different management scenarios, quantitatively assessing the impact supplemental feeding has had on the population. Our results illustrate how important long-term targeted monitoring is for robust decision making about adaptive management. © 2012 The Zoological Society of London.